1985
DOI: 10.1515/cclm.1985.23.5.259
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Plasma Amino Acids During the Oral Glucose Tolerance Test and the Effect of these Changes on Hepatic Encephalopathy

Abstract: Changes in amino acid concentrations in plasma during a 100 g oral glucose tolerance test were investigated in patients with liver cirrhosis and in healthy controls. In the controls, almost all amino acid concentrations reached a nadir about 3 hours after glucose loading, then returned to initial levels after 6 hours. Immunoreactive insulin levels reached a peak about 30 minutes aftef loading, then decreased gradually, reaching initial levels after 6 hours. In the controls, the decrease ratios/defined äs maxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…This is in agreement with previous metabolomic studies that have noted specific decreases in plasma amino acids after glucose ingestion reflecting reduced protein catabolism due to insulin action1929. Leu ( p = 1.84 E-18) had the most significant time-dependent decrease in plasma among all other polar metabolites, including Ile ( p = 2.18 E-10) and Val ( p = 4.90 E-7)2027. Also, Phe ( p = 2.87 E-12) and Met ( p = 3.08 E-12) were among the top three amino acids (after Leu) that decrease in plasma with post-prandial glucose.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is in agreement with previous metabolomic studies that have noted specific decreases in plasma amino acids after glucose ingestion reflecting reduced protein catabolism due to insulin action1929. Leu ( p = 1.84 E-18) had the most significant time-dependent decrease in plasma among all other polar metabolites, including Ile ( p = 2.18 E-10) and Val ( p = 4.90 E-7)2027. Also, Phe ( p = 2.87 E-12) and Met ( p = 3.08 E-12) were among the top three amino acids (after Leu) that decrease in plasma with post-prandial glucose.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have shown that insulin levels typically peak around 30 min after glucose loading, whereas plasma amino acids do not return to baseline until after 6 h27. Proteolysis is a pathway that is inhibited with glucose loading, resulting in selective tissue uptake of (conditionally) essential amino acids for protein biosynthesis, notably branched-chain (Leu, Ile, Val) and aromatic amino acids (Phe, Trp, Tyr), as well as Met and Lys28.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of glycolysis for BCAA catabolism is clearly evidenced by the most significant decrease in BCAA levels of all amino acids during the oral glucose tolerance test or euglycemic insulin clamp [ 42 , 43 , 44 , 45 , 46 , 47 , 48 ].…”
Section: Role Of Glycolysis and Fatty Acid Oxidation In Bcaa Catabmentioning
confidence: 99%
“…As insulin and glucagon are important hormones involved in the metabolism of amino acids, we investigated the relationship among these hormones, glucose and amino acids in plasma in liver diseases during oGrrio) 11) In this study, many significant correlations were observed among plasma Ala, Trp, Val, Lys, Glu, Tyr, His, FPG and IRG. Furthermore, we found a peculiar pattern of Ala level during OGTT only in acute hepatitis in acute stage.…”
Section: Introductionmentioning
confidence: 99%